The Neurophysiologist Perspective into MS Plasticity - Houdayer, Elise; Comi, Giancarlo; Leocani, Letizia (Frontiers in Neurology, 2015)
Multiple sclerosis (MS) is a frequent, highly debilitating inflammatory demyelinating disease, starting to manifest in early adulthood and presenting a wide variety of symptoms which are often resistant to pharmacological treatments. Cortical dysfunctions have been demonstrated to be key components of MS condition, and plasticity of the corticospinal motor system is highly involved in major MS symptoms, such as fatigue, spasticity or pain. Cortical dysfunction in MS can be studied with neurophysiological tools such as electroencephalography (EEG) and related techniques (evoked potentials – EPs) or transcranial magnetic stimulation (TMS). These techniques are now widely used to provide essential elements of MS diagnosis and can also be used to modulate plasticity. Indeed the recent development of non-invasive brain stimulation (NIBS) techniques able to induce cortical plasticity, such as repetitive TMS or transcranial direct current stimulation (tDCS), has brought promising results as add-on treatments. In this review we will focus on the use of these tools (EEG, TMS) to study plasticity in MS and on the major techniques used to modulate plasticity in MS.